Frequency of skeletal anomalies in fetal and neonatal autopsies - Radojević, Matija; Pjevčević, Katarina; Putniković, Dunja; Jevtić, Jovan; Simić, Ljubica (Medicinski podmladak, 2021)
Introduction: Skeletal anomalies are a heterogeneous group of disorders including changes in bone shape, size, and density that cause abnormalities of the extremities, trunk, and head. They rank second in Europe in the frequency of all congenital anomalies. The most common skeletal anomalies include head, face and limb anomalies. Aim: The aim of this study was to determine the frequency of skeletal anomalies and their association with anomalies of internal organs, as well as to determine the correlation between maternal age, fetal gestational week and skeletal anomalies. Material and methods: All fetal and neonatal autopsies in the period from January 1, 2018 to December 31, 2020 at the Institute of Pathology "Djordje Joannovic" of the Medical Faculty in Belgrade were analyzed. In the mentioned period, 580 fetal and neonatal autopsies were performed. Clinical data were obtained from the Gynecology and Obstetrics Clinic "Narodni Front" on the basis of completed Requests for clinical autopsy. Descriptive statistics methods were used (data are presented as absolute numbers and percentage frequencies). Results: The most common skeletal anomalies are divided into seven groups: spina bifida (20; 33.34%), limb anomalies (16; 26.67%), head and face bone anomalies (15; 25%), joint anomalies (2; 3.33%), achondroplasia (3; 5%), osteogenesis imperfecta (2; 3.33%) and other anomalies (2; 3.33%). The most common associated anomalies were CNS abnormalities, followed by heart and kidney abnormalities. The youngest mother was 15 years old, and the oldest was 47 years old. The mean age of the motheras 30 years. Conclusion: In our study, the most common anomaly is spina bifida, while limb anomalies and craniofacial anomalies are next in frequency. Skeletal anomalies were often associated with anomalies of the heart, kidneys, and CNS. They were mostly diagnosed between the 22nd and 27th gestational week. Our results show that skeletal anomalies are more common in fetuses or neonatal mothers older than 30 years.